Cyclicity of Second-hand-ness: The Language and Translation of Afrizal Malna’s “Toko Bekas Bahasa A dan B” - Zita Reyninta Sari (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Penned by the Indonesian poet, Afrizal Malna, “Toko Bekas Bahasa A dan B” is a poem with the prominent theme of second-hand-ness. This paper examines the use of language in Malna’s poem, along with its co-relation with its English translation by Gracia Asri, using translation theory from Marilyn Gaddis Rose and Lacan’s psychoanalytic theory on language and speech. Ultimately, this research found the presence of two cyclical relationships (cyclicities) in the following forms: (1) the cyclicity of language in the form of the co-dependent relationship between “problem” and “language”, made apparent by the non-normative translation of the poem, and (2) the cyclicity of language “birth” performed by characters A and B. These two cyclicities are constantly renewing themselves inside the scope of the poem.